Do sentiments influence market dynamics? : A reconstruction of the Brazilian stock market and its mood - Araújo, Tanya (2022)
Sentiments play an important role in justifying economic actions and are typically presented as being a modern incarnation of expectations that influence financial markets, whether they be of a Keynesian or other type. For the case of the São Paulo Stock Market Index (IBovespa), this paper investigates whether sentiments, as publically expressed in specialised media, represent a covariate variable which influences stock market returns, and also how market dynamics evolve through time, especially in times of major shocks or recessions. In this study we use a network approach to relate the evolution of asset returns to a sentiments index. Daily data from IBovespa and a Thomson Reuters MarketPsych index are used as fair indicators of the evolution of the Brazilian economy from 2007 to 2015. We prove that changes in market prices affect news more than the reverse.